Studying the interaction between PEX5 and its full-length cargo proteins in living cells by a novel Försteŕs resonance energy transfer-based competition assay - Hochreiter, Bernhard; Malagon-Vina, Hugo; Schmid, Johannes A.; Berger, Johannes; Kunze, Markus (Frontiers in Cell and Developmental Biology, 2022)
The import of the majority of soluble peroxisomal proteins is initiated by the interaction between type-1 peroxisomal targeting signals (PTS1) and their receptor PEX5. PTS1 motifs reside at the extreme C-terminus of proteins and consist of a characteristic tripeptide and a modulatory upstream region. Various PTS1-PEX5 interactions have been studied by biophysical methods using isolated proteins or in heterologous systems such as two-hybrid assays, but a recently established approach based on Försters resonance energy transfer (FRET) allows a quantifying investigation in living cells. FRET is the radiation-free energy transfer between two fluorophores in close proximity and can be used to estimate the fraction of acceptor molecules bound to a donor molecule. For PTS1-PEX5 this method relies on the measurement of FRET-efficiency between the PTS1-binding TPR-domain of PEX5 tagged with mCherry and EGFP fused to a PTS1 peptide. However, this method is less suitable for binding partners with low affinity and protein complexes involving large proteins such as the interaction between full-length PTS1-carrying cargo proteins and PEX5. To overcome this limitation, we introduce a life-cell competition assay based on the same FRET approach but including a fusion protein of Cerulean with the protein of interest as a competitor. After implementing the mathematical description of competitive binding experiments into a fitting algorithm, we demonstrate the functionality of this approach using known interaction partners, its ability to circumvent previous limitations of FRET-measurements and its ability to study the interaction between PEX5 and its full-length cargo proteins. We find that some proteins (SCP2 and AGXT) bind PEX5 with higher affinity than their PTS1-peptides alone, but other proteins (ACOX3, DAO, PerCR-SRL) bind with lower but reasonable affinity, whereas GSTK1 binds with very low affinity. This binding strength was not increased upon elongating the PEX5 TPR-domain at its N-terminus, PEX5(N-TPR), although it interacts specifically with the N-terminal domain of PEX14. Finally, we demonstrate that the latter reduces the interaction strength between PEX5(N-TPR) and PTS1 by a dose-dependent but apparently non-competitive mechanism. Altogether, this demonstrates the power of this novel FRET-based competition approach for studying cargo recognition by PEX5 and protein complexes including large proteins in general.